Mechanical Properties of Recycled HDPE-Areca Leaf Sheath Fiber Composite - Abdul Malek, Wan Nuradila (IRC, 2016)
Fiber reinforced-polymer composite is widely used either in engineering or non-engineering applications. The composite has to be lightweight and strong. Despite of the strength of synthetic fiber such as carbon fiber, natural fiber is preferred due to its low cost, renewability and biodegradable factors. However, limited studies were done on Areca leaf sheath fiber and recycled HDPE (rHDPE). Thus, the objectives of this project were to assess the mechanical properties including tensile, flexural and impact properties and to evaluate the effects of sodium hydroxide (NaOH) and silane treatment on the mechanical properties of the rHDPE-Areca leaf sheath fiber composite. RHDPE was selected as the matrix and Areca leaf sheath was chosen as the reinforcement with composition of 70/30 wt%. NaOH and silane treatments were performed in 5% solution concentration for 20 hours at room temperature. Twin-screw extruder was used to compound the composite while injection molding process was utilized to produce the specimens.